Raising the Bar for Public Health: Resistance Training and Health Benefits - John Tyler; Dr. Panayotis Thanos (International Universities Strength and Conditioning Association, 2023)
The major benefits of resistance training include four primary areas: cardiovascular, musculoskeletal, neuropsychological, and metabolic. Resistance exercise improves overall cardiovascular health while significantly reducing the risk of associated diseases. Cardiovascular health is specifically enhanced through the lowering of blood pressure as well as improved lipid and inflammatory profiles. Resistance training enhances musculoskeletal health through increases in bone mineral density, tendon and ligament thickness, muscle hypertrophy, and increases in balance and flexibility. Additionally, strength training provides an effective treatment option for osteoporosis, osteopenia, sarcopenia, arthritis, and low-back pain. Neuropsychologically, resistance exercise reduces anxiety, stress, and depression, while increasing cognitive function in healthy and diseased individuals. Obesity and weight management comprise the primary metabolic focus. Resistance training effectively manages weight and body fat by increasing fat-free mass, resting metabolic rate, and caloric expenditure. Overall, resistance exercise presents an effective treatment option for disease prevention and intervention by improving health and wellness.